2014
DOI: 10.1016/j.chembiol.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The Polyketide Synthase Pks13 Catalyzes a Novel Mechanism of Lipid Transfer in Mycobacteria

Abstract: Mycolate-containing compounds constitute major strategic elements of the protective coat surrounding the tubercle bacillus. We have previously shown that FAAL32-Pks13 polyketide synthase catalyzes the condensation reaction, which produces α-alkyl β-ketoacids, direct precursors of mycolic acids. In contrast to the current biosynthesis model, we show here that Pks13 catalyzes itself the release of the neosynthesized products and demonstrate that this function is carried by its thioesterase-like domain. Most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 49 publications
0
131
0
Order By: Relevance
“…[3,4] Trehalose ( 1 ), a non-mammalian disaccharide, is essential for mycobacterial viability and virulence. Trehalose is responsible for the transport of mycolic acids—long-chain (C 60 –C 90 ), α-branched, β-hydroxy fatty acids—to the exterior of the cell, where they are used to construct the thick, hydrophobic mycobacterial outer membrane, or “mycomembrane.”[5] As shown in Figure 1, cytoplasmic trehalose is converted to trehalose monomycolate (TMM),[6] which is then transported across the plasma membrane by MmpL3. [7,8] TMM is then processed by antigen 85 (Ag85) mycoloyltransferases, producing the major glycoconjugates of the mycomembrane: trehalose dimycolate (TDM) and arabinogalactan mycolate (AGM).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Trehalose ( 1 ), a non-mammalian disaccharide, is essential for mycobacterial viability and virulence. Trehalose is responsible for the transport of mycolic acids—long-chain (C 60 –C 90 ), α-branched, β-hydroxy fatty acids—to the exterior of the cell, where they are used to construct the thick, hydrophobic mycobacterial outer membrane, or “mycomembrane.”[5] As shown in Figure 1, cytoplasmic trehalose is converted to trehalose monomycolate (TMM),[6] which is then transported across the plasma membrane by MmpL3. [7,8] TMM is then processed by antigen 85 (Ag85) mycoloyltransferases, producing the major glycoconjugates of the mycomembrane: trehalose dimycolate (TDM) and arabinogalactan mycolate (AGM).…”
Section: Introductionmentioning
confidence: 99%
“…6,22,24,31 In an important pathway, trehalose is also lipidated, undergoing 6- O -mycoloylation by Pks13 to generate trehalose monomycolate [TMM ( 4 ), structure shown in Figure 1]. 32 After crossing the plasma membrane via MmpL3, 33,34 TMM donates its 6- O -mycoloyl group to two major acceptor molecules in service of constructing the unique mycobacterial outer membrane, or “mycomembrane.” These processes, which are catalyzed by the Ag85 complex, involve mycoloyl group transfer to either (i) terminal residues of the arabinogalactan polymer, generating arabinogalactan-linked mycolates (AGM); or (ii) a second molecule of TMM, generating trehalose dimycolate [TDM ( 5 ), shown in Figure 1]. 35–37 AGM is the foundational inner leaflet component of the mycomembrane, while TDM resides in the mycomembrane’s outer leaflet and is an important contributor to mycobacterial pathogenesis.…”
Section: Trehalose Metabolism In Naturementioning
confidence: 99%
“…This step is followed by reduction of a keto moiety by CmrA to produce TMM, a MA carrier. 33 MmpL3 transports TMM from the cytoplasm to the periplasm. 34 The TMM is utilized by the Ag85 complex for biosynthesis of TDM and mAG and releases free trehalose in pseudoperiplasmic space.…”
Section: Trehalose Utilization Pathways (Tups)mentioning
confidence: 99%
“…72 Gavalda et al recently reported that Pks13 would not release hydrophobic α-alkyl β-ketoacids ( 29 ) into bacterium instead, it transfers to trehalose via the Pks13 thiosesterase domain to produce the keto form of TMM ( 31 , TMM k), which when reduced by CmrA to afford TMM ( 32 ). 33 …”
Section: Trehalose Utilization Pathways (Tups)mentioning
confidence: 99%